(untitled) (Semiárida, 2022)
The tools that a professional has when carrying out a strategic analysis of a subject/object of study are varied and diverse, in general, each one specialized in specific aspects, without a global and systemic view. The objective of this work is to design, integrate and apply an integrative model of strategic analysis, applied to the agroindustrial biodiesel sector of the province of La Pampa. A cross-sectional analysis was generated that allowed a broad and dynamic, not so static, look at the variables. For a better understanding, the application of the model to the biodiesel complex in the province of La Pampa is proposed, which will allow in a graphic and visual way to understand the dynamics and usefulness of the tool. As a conclusion of the work, a comprehensive analysis model was developed that allowed its correct application and provided enriching results for the strategic analysis. Director: Ferro Moreno, Santiago Co-director: Mariano, Roberto Carlos